INITIATING MULTICULTURAL EDUCATION IN INDONESIAN COMMUNICATION STUDIES - Fajar Junaedi; Aswad Iskak (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2015)
The issue of multiculturalism into a time bomb that exploded after the 1998 reform. The various conflicts that contains multicultural sentiment as happened in Ambon, Poso and Sambas proof multicultural issues in Indonesia. In relation to communication, multicultural conflict is inseparable from the role of opinion leaders who communicate ideas and ideas on the audience and also how the mass media do multicultural framing the conflict that occurred. An important role of communication in the realm of multicultural issues is the position of higher education is becoming increasingly significant communication sciences. Communication studies in Indonesia is in the face of communication seen stuttering multicultural issues that occur. This bias was also not released from the state of higher education before the reform of science communication is dominated by a paradigm that was developed to emphasize the New Order developmental models. In the New Order era, multicultural issues covered by the government and if the emerging multicultural issues through the repressive military government officials and leading into the solution. This condition is different from the post-reform era, when transparency of information and communication occurs. Multicultural issues can no longer be solved by the approach of state power but should involve civil society. Involving civil society is an open communication opportunities for higher education to contribute in the insertion of multiculturalism in education. This paper attempts to examine how multiculturalism should insertion of communication in higher education in Indonesia, so the higher education of communication is able to produce graduates who are competent communication with multicultural perspective.